On the Role of Teachers’ Professional Identity and Well-Being in Their Professional Development - Zhao, Qian (Frontiers in Psychology, 2022)
In the former twenty years, professional identity has arisen as a different study domain in the area of language instruction and education. Educators’ professional identity frames educators’ explanation of their functions, academic changes, and alterations in syllabi, class exercises, utilization of approaches and strategies, and their connection to other problems in the academic setting. Also, well-being is one of the elements whose influence and connection with identity are noted in various studies. However, their roles in professional development have not been examined so this review of literature aims to investigate the role of these constructs in professional development which is regarded as a noteworthy aspect of teacher quality. In a nutshell, some implications are proposed for the scholastic stakeholders.